Spatial and social changes caused by the continuous exploitation of lignite in the Kolubara lignite basin, Serbia - Đukičin, Smiljana; Đorđević, Jasmina; Milanković, Jelena (Acta geographica Slovenica, 2014)
The Kolubara Lignite Basin in the Republic of Serbia is the most important source of this type of fossil energy. Available lignite reserves enable the production of electricity, so the priority, in this region, is its exploitation. This is the reason why all other characteristics of this region have undergone major changes. Since the lignite exploitation started, the land use and river courses have changed in the region, local communities have been moved out, the settlements, infrastructure and human activity have been altered. The whole landscape acquired a completely different image. The social aspect is a sensitive and delicate feature, but the regulation of the region is also significant. Local population in this region has faced a set of social, cultural and economic problems.